(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The catalytic activity and surface properties of supported on silicon carbide Cu-Co-Fe oxide catalysts in the reaction of CO oxidation is studied. It is determined, that for the sample with 10 % mass of active phase maximum catalytic activity is observed. Thermodesorption investigations have been shown, that increase of catalytic activity correlates with increasiny of quantity of the low-temperature α2-form of СО2 .